Medical Comfort at the Intersection of Sexual Orientation and Gender Identity. (October 2019) - Oyarvide Tuthill, Zelma; Gorman, Bridget
Effective and comfortable provider-patient communication is associated with engagement in health-promoting behavior. Although research on medical experiences among sexual minorities has increased, work has not examined how gender intersects with sexual identity to shape medical experiences. Using an intercategorical intersectional approach, we examine whether sexual minorities perceive their medical provider as knowledgeable and comfortable with their sexual identity, and how these relationships differ for cisgender men, cisgender women, and multigendered transgender adults. Drawing on data from 3, 050 adults included in the 2010 Social Justice Sexuality Project, logistic regression models show three main findings. First, compared with heterosexual cisgender women, bisexual cisgender women are less likely to perceive that their provider knew their sexual identity—and if they did perceive knowledge, they were less likely to perceive that their provider was comfortable with their sexual identity. Second, gay transgender adults have significantly lower odds of perceiving provider comfort with their sexual identity relative to heterosexual transgender adults. Finally, for each gender group, our models demonstrated the importance of medical and social relationships for perceiving both knowledge and comfort with sexual identity from medical care providers.